Waqf fundraising strategy for islamic boarding’s independence - Mohammad Noviani Ardi; Dina Yustisi Yurista; Suci Ramadhan (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
The purpose of this paper is to find out the fundraising of waqf fund strategy conducted by Tazakka, Modern Boarding School, also to know how effective the implementation of these strategies in realizing the independence of this boarding school. This research uses quantitative research with descriptive approach that relies on primary data sourced from interviews. This paper interpreted the management of waqf funds in Tazakka Boarding School which consist the procedures of waqf association and effectiveness of waqf fund management to realize the independence of boarding school. Moreover, these findings reveal that the effective mechanisms involved in raising waqf funds, in turn, lead to the enhancement of the roles and functions of waqf institutions to build modern educational institutions today.